(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2022)
The study’s problem is to know the availability of the elements of applying forensic accounting to detect cases of financial fraud in Libya, and thus the study aimed to find out the availability of Academic and practical qualifications, as well as the availability of skills and experience necessary for the application of forensic accounting. To achieve the objectives of the study, a questionnaire was designed as a means of collecting primary data related to the subject of the study and then unloading and analyzing them using the SPSS statistical program and using appropriate statistical tests and treatments in order to reach valuable indications that support the subject of the study. The study concluded that there are elements for applying forensic accounting in Libya, and there are difficulties that limit its application. in the Libyan environment